Impact of greenspaces in city on avian species richness and abundance in Northern Africa - (:unkn) unknown (My University, 2017)
Increasing urbanization is a major challenge in the context of global changes, because this environment is known to negatively impact biodiversity. It is therefore important to identify factors maintaining biodiversity in such areas. Here, we tested in 650 sites whether the greenspaces in urbanized area of Annaba (Algeria) has positive effects on avian species richness and abundances. Our results show that species detection (n = 26) is more important during the breeding season as compared to the winter season, and that avian species richness is positively affected by the greenspaces. For most species, greenspaces impact positively their presence and abundances. Only the feral pigeon was less detected in greenspaces as compared to built-up areas. Our study therefore confirmed, for the first time in a Northern African city, that greenspaces significantly increase the species richness and abundances of birds, and shows that the season can profoundly affect such indicators.
Keywords: African Research